2022
DOI: 10.3390/cells11071202
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Selected D2 Dopaminergic Receptor Agonists on VEGF-Dependent Neovascularization in Zebrafish Larvae: Potential New Therapy in Ophthalmic Diseases

Abstract: Pathological angiogenesis is correlated with many ophthalmic diseases. The most common are exudative age-related macular degeneration and proliferative diabetic retinopathy. The current treatment for these diseases is based on regularly administered anti-VEGF antibodies injections. In the study, we investigated selected D2 dopaminergic receptor agonists, namely bromocriptine, cabergoline and pergolide, on hypoxia-induced neovascularization. We used the zebrafish laboratory model, specifically three-day post fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In a study with a zebrafish animal model, retinal neovascularization induced by cobalt chloride promoted hypoxia. Pre-incubation with bromocriptine, cabergoline, pergolide, and all ergot-derived D2 dopamine receptor agonists significantly inhibited abnormalities of angiogenesis, decreasing mRNA expression levels of vascular endothelial growth factor Aa (VEGFAA) [ 130 ].…”
Section: Drugs and Medicinementioning
confidence: 99%
“…In a study with a zebrafish animal model, retinal neovascularization induced by cobalt chloride promoted hypoxia. Pre-incubation with bromocriptine, cabergoline, pergolide, and all ergot-derived D2 dopamine receptor agonists significantly inhibited abnormalities of angiogenesis, decreasing mRNA expression levels of vascular endothelial growth factor Aa (VEGFAA) [ 130 ].…”
Section: Drugs and Medicinementioning
confidence: 99%
“…This study also showed that DRD2 expression was increased in the low concentration atropine group compared with the control group, and the indirect activation of DRD2 resulted in the decrease of CNV area and VEGFA expression. Recently published a study on fundus neovascularization found that D2 dopaminergic receptor agonists can downregulate VEGF overexpression and should be taken under consideration as new anti-VEGF drug used in ophthalmological vasculature diseases, such as age-related macular degeneration and proliferative form of diabetic retinopathy and diabetic macular edema [9] . Although the level of VEGF in myopia CNV eyes was lower than that in normal…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine functions through its corresponding membrane receptors, a family of seven transmembrane regions of G-protein-coupled receptors that dopamine receptor into five major subtypes, they were D1-class receptors (D1, D5) and D2-class receptors (D2, D3, D4) [8] . D2 dopaminergic receptor agonists can downregulate VEGF overexpression and should be taken under consideration as new anti-VEGF drug used in ophthalmological vasculature diseases, such as agerelated macular degeneration and proliferative form of diabetic retinopathy and diabetic macular edema [9] . Therefore, low concentrations of atropine may indirectly affect pathological neovascularization of the ocular fundus.…”
Section: Metformin Inhibits Subretinal Fibrosismentioning
confidence: 99%
“…As tumor cells injected into the yolk can enter the circulation, go to the tailfin, and create micro-metastases, intravasation has also been observed [128]. Important discoveries regarding the mechanics of sprouting angiogenesis [138][139][140][141], vessel guidance [135][136][137][138][139][140][141][142], and vascular endothelial growth factor signaling [143,144], among other angiogenic processes [145], have been made thanks to the use of zebrafish. Time-lapse imaging can reveal information on the activities of cancer cells and suggest pathways for invasion, proliferation, and metastasis.…”
Section: Embryo-larval Zebrafish Xenograftsmentioning
confidence: 99%